Legal Standing of Insurance Policy Holders Regarding Applications for Delay of Debt Payment Obligations Due to Bankruptcy (Study of Commercial Court Decision Case Number 389/Pdt.Sus-pkpu/2020/Pn-Niaga.Jkt.Pst) - Aji Titin Roswitha Nursanthy; Kurniawan, Dodi; Hindarsah, Yuliana (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The proposed study will examine the legal protections afforded to insurance policyholders if their insurance provider declares bankruptcy. 2) In accordance with Case Decision No. 389/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst., this research will analyze and determine the legal standing of policyholders regarding requests to postpone debt payment obligations resulting from bankruptcy. With a focus on both statutes and concepts, this study follows a normative juridical research methodology. According to the research, Article 53 of Law Number 40 of 2014 on Insurance provides legal protections for policyholders of insolvent insurance companies. In the same decision, the Panel of Judges confirmed that PT. Kresna Life Insurance (in PKPU) and all its creditors are bound by a settlement agreement, which includes mechanisms that protect policyholders from insolvency, such as actio pauliana, alignment of receivables, and settlement (peace). Law No. 37 of 2004 on Bankruptcy and Postponement of Debt Payment Obligations (PKPU) states that the signing of the peace agreement will officially end the PKPU. Additionally, in the same decision, insurance policyholders are considered preferred creditors in requests for the deferral of debt payment obligations due to bankruptcy. Due to the specifics of their receivables, certain creditors are required by law to be paid first before others. These creditors are known as preferred creditors, who have special rights under the law, giving them priority over other creditors based on the nature of their receivables.